MALAYSIA'S MINIMUM WAGE POLICY: ECONOMIC SECURITY PERSPECTIVE - SITI HAWA, MOHD ANUAR (Universiti Malaysia Sarawak (UNIMAS), 2021)
People should be able to consistently access all of their needs as defined by economic security. It is critical for individuals and nations to evaluate national security because it is linked to the concept of economic well-being. Climate change, COVID-19, and significant technological changes have all contributed to an increase in economic insecurity in recent years. On the other hands, The Malaysian Minimum Wage has become a hot topic in the country in recent years due to its slow increase, which is insufficient to keep up with the rising cost of living in Malaysia. The problem is getting worse as the world is gripped by the deadly COVID 19 pandemic, which is taking lives, jobs, and a peaceful way of life. COVID 19 has halted many economic sectors, threatening national and global economies. Despite rising living costs and COVID 19, Malaysia's minimum wage remains low and not comparable. Furthermore, the impact and struggle of each Malaysian employee varies according to their minimum wage income class, which is divided into three groups: T20, M40, and B40. As a result, it is critical to investigate the impact on workers in Malaysia by income class in order to develop comprehensive solutions to the problem of low minimum wage rates in Malaysia. Moreover, these studies include Max Weber's surplus theory of wages, which investigates how a labourer would receive a subsistence wage in exchange for work